53rd AIAA/ASME/ASCE/AHS/ASC Structures, Structural Dynamics and Materials Conference<BR&amp;gt;20th AIAA/ASME/AHS Adapti 2012
DOI: 10.2514/6.2012-1650
|View full text |Cite
|
Sign up to set email alerts
|

Micromechanics of Fatigue Damage in Unidirectional Polymer Composites

Abstract: A work in progress is described that so far includes a finite element (FE) micromechanics modeling capability that generates random distributions of fibers in a periodic unit cell to predict fatigue damage in the matrix. The FE micromechanics model has automated features that facilitate parametric studies. This includes the ability to simulate any three-dimensional macroscopically uniform state of stress and to generate new fiber distributions within random-periodic unit cells that can have variable numbers of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…Different from the work reported previously [4], here we used the theory of yielding and failure for isotropic materials described by Christensen [7]. To date, we have restricted use to the form previously described by Raghava et al [8] as shown in Eq.…”
Section: Fatigue Failure Modelingmentioning
confidence: 98%
See 4 more Smart Citations
“…Different from the work reported previously [4], here we used the theory of yielding and failure for isotropic materials described by Christensen [7]. To date, we have restricted use to the form previously described by Raghava et al [8] as shown in Eq.…”
Section: Fatigue Failure Modelingmentioning
confidence: 98%
“…Study of fatigue at the micro-stress level will help to understand how to formulate composite level fatigue models for application in full scale structural analysis. Micromechanics of random fiber distributions also permit study of the effect of fiber distribution and other material parameters at the micro-scale on fatigue damage evolution and fatigue life [4].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations